2018
DOI: 10.14814/phy2.13602
|View full text |Cite
|
Sign up to set email alerts
|

Role of afferent and efferent renal nerves in the development of AngII-salt hypertension in rats

Abstract: Hypertension is the leading modifiable risk factor for death worldwide, yet the causes remain unclear and treatment remains suboptimal. Catheter‐based renal denervation (RDNX) is a promising new treatment for resistant hypertension, but the mechanisms underlying its antihypertensive effect remain unclear. We recently found that RDNX attenuates deoxycorticosterone acetate‐salt hypertension and that this is dependent on ablation of afferent renal nerves and is associated with decreased renal inflammation. To det… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
11
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 37 publications
(102 reference statements)
3
11
1
Order By: Relevance
“…In this context, important is also our finding that RDN significantly decreased BP in sham-operated TGR but not in ACF TGR. This suggests that in TGR, hypertension is associated with increased RSNA, an important finding which contradicts the conclusion from the studies using chronic ANG II infusion [16, 19, 45] that ANG II-dependent hypertension is accompanied by low RSNA and that RDN would not reduce BP in this model. The present findings indicate that this paradigm should be reconsidered.…”
Section: Discussioncontrasting
confidence: 72%
“…In this context, important is also our finding that RDN significantly decreased BP in sham-operated TGR but not in ACF TGR. This suggests that in TGR, hypertension is associated with increased RSNA, an important finding which contradicts the conclusion from the studies using chronic ANG II infusion [16, 19, 45] that ANG II-dependent hypertension is accompanied by low RSNA and that RDN would not reduce BP in this model. The present findings indicate that this paradigm should be reconsidered.…”
Section: Discussioncontrasting
confidence: 72%
“…However, in this investigation, the absence of renal nerves did not prevent DEX-induced hypertension. These results are consistent with earlier reports where RDNX was not able to eliminate blood pressure elevations in the Dahl NaCl-sensitive rats (Wyss et al, 1987) and salt-sensitive-related hypertension (Foss et al, 2018; Tudorancea et al, 2018). Actually, RDNX exacerbates the response to DEX (Figure 1B); that may be associated with an increase in vascular reactivity.…”
Section: Discussionsupporting
confidence: 93%
“…For example, RDN in rats did not attenuate HT caused by chronic ANG II infusion or by salt loading and reduced kidney mass. 85,89 In rabbits, RSNA is suppressed in ANG II HT and RDN does not attenuate the HT. 86,87 In dogs, RSNA is not increased in ANG II HT 18,22 and RDN did not substantially ameliorate HT caused by renal artery stenosis 91,92 or by chronic aldosterone infusion.…”
Section: Renal Denervation For Hypertension Therapy Rationale For Rdnmentioning
confidence: 97%
“…Previous studies in experimental animals have shown that RDN has little effect on BP in models of HT with normal/low sympathetic activity such as HT induced by chronic infusion of ANG II or aldosterone, renal artery stenosis, or salt loading in animals with reduced nephron numbers. 62,85,[87][88][89]137 Secondary analyses of data from SYMPLICITY HTN-3 also suggest that RDN may be less effective in patients who have volume-dependent forms of HT. 63 In contrast, RDN has been shown to be highly effective in reducing BP in obesity-induced HT which is associated with increased RSNA and may account for 65-75% of the risk for primary HT as well being a major contributor to treatment resistant HT.…”
Section: In Which Patients Is Rdn Most Likely To Effectively Reduce Bp?mentioning
confidence: 99%